MO075DNA METHYLATION AND RESPONSE TO STEROIDS IN CHILDREN WITH NEPHROTIC SYNDROME. (6th June 2020) - Hayward, Samantha; Suderman, Matthew; Bierzynska, Agnieszka; Welsh, Gavin I; Saleem, Moin A
Abstract: Background and Aims: Historically, paediatric patients with nephrotic syndrome (NS) have been crudely categorised by their response to steroids: steroid resistant (SRNS), steroid sensitive (SSNS) and secondary SRNS. However, growing evidence that these categories do not correspond to single diseases has led to a demand that they be re-defined based on biological mechanisms involved in the disease process. Indeed, next generation sequencing has identified causative mutations in up to 30% of paediatric NS patients ('monogenic' NS); however, specific disease mechanisms in the remaining patients remain unknown. We propose that the remaining phenotype variation in NS may be explained by DNA methylation, the reversible but heritable addition of methyl groups to DNA that change how the underlying DNA sequence is interpreted.